2016
DOI: 10.29406/182
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Belajar Siswa Dalam Memahami Materi Invertebrata Di Kelas X Man 2 Pontianak

Abstract: Berdasarkan  hasil  wawancara  terhadap  guru  biologi  di  kelas  X  MAN  2  Pontianak  pada  tahun  ajaran 2014/2015, diketahui adanya permasalahan kesulitan belajar siswa pada materi invertebrata. Tujuan dari penelitian ini adalah untuk menganalisis kesulitan belajar siswa dalam memahami materi invertebrata.Metode yang  digunakan  adalah  metode  deskriptif.Subjek  penelitian  adalah  siswa  kelas  XI  IPA  1  berjumlah  3 3 siswa.Subjek penelitian ditentukan berdasarkan teknik purposive sampling.Kesulitan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
2
0
8
Order By: Relevance
“…In short, it can be concluded that Latin terms can cause the students learning difficulties. According to the research finding who conducted by Alawiyah et al (2016) [16] states thet the types of learning difficulties experienced who face by students in understanding the material of invertebrates at class X MAN 2 Pontianak are difficulties in understanding the scientific names until more than half of respondent or 59.74%, difficulties in understanding concepts faced by almost half of respondent or 40.15%, and difficulties in understanding the term faced by 26.66% respondents. In line with this statement, the research finding who conducted by Rusgiarti in Nurbaiti (2017) [15] also emphasized that the low ability to remember and to memorize the scientific names and Latin terms is one of the characteristics of student learning difficulties in Biology subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In short, it can be concluded that Latin terms can cause the students learning difficulties. According to the research finding who conducted by Alawiyah et al (2016) [16] states thet the types of learning difficulties experienced who face by students in understanding the material of invertebrates at class X MAN 2 Pontianak are difficulties in understanding the scientific names until more than half of respondent or 59.74%, difficulties in understanding concepts faced by almost half of respondent or 40.15%, and difficulties in understanding the term faced by 26.66% respondents. In line with this statement, the research finding who conducted by Rusgiarti in Nurbaiti (2017) [15] also emphasized that the low ability to remember and to memorize the scientific names and Latin terms is one of the characteristics of student learning difficulties in Biology subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai KKM yang ditetapkan sekolah yaitu 75.Keterlibatan guru dalam suatu proses pembelajaran sangat berpengaruh terhadap berlangsungnya kegiatan pembelajaran di kelas, sehingga pembelajaran tidak hanya didominansi oleh peserta didik yang memiliki kemampuan yang lebih tinggi. Menurut (Alawiyah et al, 2016) guru merupakan faktor yang penting untuk mengatasi kesulitan belajar peserta didik. Usaha yang dapat dilakukan guru untuk meningkatkan kemampuan kognitif peserta didik diantaranya dengan menggunakan teknik pembelajaran yang tepat.…”
Section: Pendahuluanunclassified
“…Kesulitan belajar akan mengganggu aktivitas pembelajaran pada siswa karena tersebut siswa menjadi malas untuk berpikir dalam menyelesaikan soal, sehingga perlunya untuk mengetahui kesulitankesulitan yang dialami oleh siswa ketika menyelesaikan soal supaya dapat meminimalisir kesulitan yang dialami. Hal ini sesuai dengan penelitian (Alawiyah et al, 2016) bahwa apabila kesulitan belajar tidak segera diatasi maka proses penerimaan pengetahuan baru akan terusmenerus selalu mengganggu siswa.…”
Section: Pendahuluanunclassified